(untitled) (Jurnal Bahasa, 2025)
Speeches delivered by political leaders often serve as a medium for identity construction, and one of the ways this is achieved is through the use of personal pronouns. This study aims to identify the types of personal pronouns used in Movement Control Order (MCO) special address texts and to examine the identities constructed by the speaker in relation to the citizens. A total of nine speech texts were downloaded from the official website of the Prime Minister’s Office – https://www.pmo.gov.my/speech/, spanning from March 2020 to February 2021. Employing both qualitative and quantitative approaches, this study applied Fairclough’s (2013) model of Critical Discourse Analysis. The findings indicate three types of personal pronouns used: "kita" (we), "saya" (I), and "kerajaan" (the government). The personal pronouns "kita" recorded the highest usage frequency, appearing 284 times (51.08%), followed by "saya" with 189 times in usage (33.99%), and "kerajaan" with 83 times (14.93%). The predominant use of "kita" illustrates the speaker’s intention to construct a collective identity, fostering a sense of solidarity with the people. The use of "kita" aligns with the contextual urgency of the pandemic, signifying a call for shared responsibility in curbing the spread of COVID-19. In sum, the analysis reflects a strategic discursive effort to promote unity and collective social action during a global health crisis. Keywords: Covid-19, identity, Movement Control Order (MCO), Prime Minister of Malaysia, personal pronouns, speech text Full text: PDF